Histopathological aspects and staging systems in non-traumatic femoral head osteonecrosis: an overview of the literature - Di Benedetto, Paolo; Niccoli, Giuseppe; Beltrame, Alessandro; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2016)
Background: The pathogenesis of non traumatic osteonecrosis of the femoral head (ONFH) has not yet been established. The literature shows a variable nomenclatura for this condition that often leads to confusion. Several risk factors have been identified but histopathological and radiological outcomes are common. Purpose: To provide the overview on the current knowledges about the nomenclatura, etiology, disease progression, relationship between histopathological changes and imaging techniques in order to stage the disease accurately. Etiology and pathogenesis: Genetic predisposition, metabolic factors, local factors affecting blood supply such as vascular damage, increased intraosseous pressure and mechanical stress are involved in this desease. The final results are bone ischemia and infarction getting bone deathand FH collapse. Histopathological aspects and staging systems: Several staging systems have been developed to stage ONFH based on imaging techniques.The subchondral collapse, the size or quantification of the lesion, and the lesion location within the femoral head are identified as the most important prognostic factors in ONFH disease. Histological analysis plays a critical role to evaluate the quality of necrotic area and the differences between microscopic, macroscopic and imaging outcomes were detected. Conclusions: an ideal staging system is necessary to stage ONFH desease to detect several aspects, but itìs more difficult to create. At the present time we summarize some aspects that are advisable to focus during ONFH for the correct treatment.